Midterm results of mitral valve repair with lifting annuloplasty strip for acute phase infective endocarditis. Issue 1 (December 2015) - Lee, Sung; Yang, Hyun; Kim, Jun; Shin, Je; Son, Jae; Song, Meong; Chee, Hyun
Abstract Background Mitral valve repair is favored over replacement due to superior outcomes. However, extensive infective endocarditis (IE) often has been considered unreconstructable. We retrospectively analyzed the mid-term outcomes of an individualized repair approach using a lifting annuloplasty strip. Methods Between December 2007 and March 2014, 27 consecutive patients with acute single mitral valve IE (age 43 ± 16 years, 11 men) underwent lifting mitral annuloplasty (LMA) with a strip (Mitracon® strip, 28 mm in 4, 32 mm in 10, and 34 mm in 13). Blood culture was positive in 70 % (Streptococcus 10, Staphylococcus 4, HACEK 3, Enterococcus 1, Gram negative bacilli 1). One case (4 %) had a previously repaired mitral valve—the repair was redone. Via right thoracotomy (74 %) or median sternotomy (26 %), repair was performed by removal of vegetation and resection of infected tissue, the defect typically then being repaired using a bovine pericardial patch (81 %). Artificial chordae were formed in 5 patients. Nine (33 %) of them had posterior leaflet augmentation (PLA) to get sufficient coaptation height. Clinical and echocardiographic follow-up were performed. Results Compared with preoperative ones, postoperative echocardiograms revealed decreases of left ventricular (LV) end-diastolic dimensions (57.2 ± 6.3 versus, 45.4 ± 6.2, or 44.8 ± 4.1 mm, allp < 0.01). The LV ejection fraction decreased immediately, but recovered (64.4 ± 9.6 % vs. 54.5 ± 9.8 %, or 65.2 ± 6.1 %, p = 0.002, p = 1.000, respectively). The latest follow-up echocardiograms (median 28 months) universally showed no or minimal regurgitation, with a preserved mitral valve opening area (2.27 ± 0.48 cm2 ). During the clinical follow-up (median, 54 months), one (3.7 %) death was observed (in-hospital, due to biliary sepsis and pneumonia). There was no reoperation or major cardiovascular event. The 5 year survival rate was 96.3 %. Conclusions The repair technique of LMA and/or PLA in patients with IE achieved good structural and functional outcomes as well as an excellent 5 year survival rate. An individualized repair approach should be recommended in patients with acute phase IE.